Prognostic Utility of the Ratio of Pulmonary Artery Diameter to Ascending Aorta Diameter in COVID-19 Patients - Mustafa Öcal; Togay Evrin; İlayda Çetin (Eurasian Journal of Emergency Medicine, 2023)

(untitled)
Aim: Numerous hospital admissions of patients infected with Coronavirus disease-2019 (COVID-19) reveal the importance of managing clinical, radiological, and laboratory findings related to disease severity and mortality. Pulmonary artery (PA) trunk enlargement is a well-known indicator of hemodynamic instability. The purpose of this study was to assess the prognostic value of PA trunk diameter enlargement and the ratio of the PA diameter to the ascending aorta (AA) diameter on unenhanced computed tomography images in patients with severe COVID-19 infection. Materials and Methods: Three hundred and ninety-three hospitalized patients in the pandemic ambulatory service, emergency department, and intensive care unit were retrospectively analyzed. Correlations between the PA diameter and the ratio of the PA diameter to the AA diameter with prognostic factors and values were examined. Results: PA/AA rates were significantly higher in hospitalized patients who developed mortality. The optimum cut-off PA/AA ratio to predict mortality was 0.9386, with a sensitivity of 98% and specificity of 97%. The optimum cut-off PA diameter to predict mortality was 3.315 cm, with a sensitivity of 98% and specificity of 89%. The mortality risk was 221 times higher in patients with a PA/AA ratio higher than 0.93 and 65 times higher in patients with a PA diameter greater than 3.315 cm. Conclusion: PA trunk diameter enlargement and the PA/AA diameter ratio can be valuable markers for predicting the mortality risk of COVID-19.